Comparative analysis of triage systems at emergency departments of different countries: Implementation in Kazakhstan - Lyudmila Pivina; Assylzhan M. Messova; Yersin T. Zhunussov; Zhanar Urazalina; Zhanna Muzdubayeva; Diana Ygiyeva; Murat Muratoglu; Gulnara Batenova; Sharbanu Uisenbayeva; Yulia Semenova (Russian Open Medical Journal)
Medical sorting is aimed at assessment of disease severity and has to be carried out within a short time to determine the priorities for patient care and transportation to the most appropriate place for future treatment. The goal of this study was to provide an integrative review by analyzing the publications on the most common triage systems worldwide in order to select and implement the most reliable system at emergency departments. We searched for publications relevant to our comparative analysis in evidence-based medicine databases. A total of 1,740 literary sources were identified, of which 42 were selected for analysis. Comparative analysis of different triage systems may help implementing the most efficient system in Kazakhstan. The Emergency Severity Index is considered the most reliable and accurate tool used in international practice, and it could provide a basis for introduction of triage system at emergency departments in Kazakhstan.